Pengaruh Software SAP Dalam Meningkatkan Kinerja Karyawan Bagian Keuangan Dan Akuntansi Pada PT. Perkebunan Nusantara VI - Alda Fitrisiah; Heriyani (Journal of Applied Accounting And Business, 2021)
A Employee performance is of course one of the important components for the company because it affects the company's operations. This study aims to analyze the effect of SAP software in improving employee performance in finance and accounting at PT. Perkebunan Nusantara VI, used a questionnaire as an instrument to take a sample of 30 respondents. The analytical method used in this research is multiple linear regression analysis. The independent variables in this study are software quality, information quality, software user satisfaction and the impact of using accounting software, while the dependent variable is employee performance of 65.3%, the remaining 34.7% is influenced by other variables. The results of this study indicate that the variables of software user satisfaction and the impact of using accounting software have a significant effect on employee performance with a significant value <0.05 with a value of Tcount < Ttable (-2.182 < 2.060) and (6.064 > 2.060). Meanwhile, the variables of software quality and information quality have no effect on employee performance because they have a significant value > 0.05 with a value of Tcount < Ttable (-0.293 < 2.060) and (-1.347 < 2.060). For the overall effect, the value of Fcount > Ftable is (11.870 > 2.76) with a significant value of 0.000 <0.05.